2013
DOI: 10.3354/meps10439
|View full text |Cite
|
Sign up to set email alerts
|

Wintering eiders acquire exceptional Se and Cd burdens in the Bering Sea: physiological and oceanographic factors

Abstract: During late winter (March) in the Bering Sea, levels of Se in livers and Cd in kidneys of spectacled eiders Somateria fischeri were exceptionally high (up to 489 and 312 µg g −1 dry mass, respectively). Comparison of organ and blood samples during late winter, early spring migration, and breeding suggests that the eiders' high Se and Cd burdens were accumulated at sea, with highest exposure during winter. High exposure may have resulted from high metabolic demands and food intake, as well as concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 86 publications
(146 reference statements)
0
15
0
Order By: Relevance
“…Moreover, once the range of possible diets for component taxa are known, research emphasis might shift to understanding effects of major disturbances, dispersal timing and processes, and early survival of settling larvae as drivers of food web structure in different areas (Oliver et al, 1985;Hunt and Mullineaux, 2002;Conlon and Kvitek, 2005;Palumbi and Hedgecock, 2005). These stochastic processes also include abiotic factors that determine the timing, magnitude, and subsequent lateral advection of fresh microalgae settling from the water column (cf., Hunt et al, 2009;Brown and Arrigo, 2013;Lovvorn et al, 2013b). Although such abiotic processes might be mostly stochastic, trends in their frequency and intensity can perhaps result in directional change in food web structure and function.…”
Section: A Mostly Stochastic System?mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, once the range of possible diets for component taxa are known, research emphasis might shift to understanding effects of major disturbances, dispersal timing and processes, and early survival of settling larvae as drivers of food web structure in different areas (Oliver et al, 1985;Hunt and Mullineaux, 2002;Conlon and Kvitek, 2005;Palumbi and Hedgecock, 2005). These stochastic processes also include abiotic factors that determine the timing, magnitude, and subsequent lateral advection of fresh microalgae settling from the water column (cf., Hunt et al, 2009;Brown and Arrigo, 2013;Lovvorn et al, 2013b). Although such abiotic processes might be mostly stochastic, trends in their frequency and intensity can perhaps result in directional change in food web structure and function.…”
Section: A Mostly Stochastic System?mentioning
confidence: 98%
“…One possible change is in organic matter supply. Such change could result from altered sea ice patterns which affect the timing, duration, or magnitude of microalgal blooms (ice algae and phytoplankton), or from shifts in wind-driven currents that redistribute settled bloom material Brown and Arrigo, 2013;Lovvorn et al, 2013b). Another expected change is increased water temperature, which could alter the species composition, abundance, or metabolic demands of predators or prey.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We also found that the abundance and dispersion of species and sizes of bivalves had changed substantially over the preceding decade (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)). These changes probably resulted from wind-driven shifts in water movements that alter the grain size and organic content of sediments, advection and settlement of larvae, and possibly abundance of other predators that compete for the same prey (Kolts 2012, Lovvorn et al 2013). Thus, when projecting the adequacy of habitat in protected areas for bottom-feeding endotherms, one must consider not only trends in total ice extent, but also possible shifts in winds that can greatly alter both the dispersion of food and its accessibility relative to ice concentrations (Danielson et al 2011(Danielson et al , 2012.…”
Section: Temperature and Wind Effects On Ice Conditionsmentioning
confidence: 99%
“…Endangered Species Act (ESA), which requires delineation and protection of Critical Habitat for species that are listed. The wintering area of Spectacled Eiders, as well as the migration and molting areas in Norton Sound and the northeast Chukchi Sea, are designated Critical Habitat for this species (see Lovvorn et al 2009Lovvorn et al , 2013. The ESA, along with the Marine Mammal Protection Act (MMPA) and provisions for Essential Fish Habitat under the Magnuson-Stevens Act, are the main U.S. federal laws that mandate creation of protected areas, with a focus on particular species in certain places.…”
Section: Introductionmentioning
confidence: 99%